Importancia de la implementación de tensiómetros en el manejo del agua de riego a nivel parcelario - Verdezoto Paredes, Andy Fabricio (2024)
Tensiometers measure the soil matrix potential, this tool is located close to the root zone and at a varying depth of the crop to be analyzed, if the extraction force is close to zero it is interpreted that the soil is saturated and does not need irrigation, but if values far from zero are present, irrigation should be carried out, thus establishing the moment when the crop needs water. The objective of this research is to analyze the importance of the use of the tensiometer in irrigation water management at the plot level. This work was developed as non-experimental bibliographic research using the technique of analysis, journals, current texts, articles, synthesis and summary of the data collected. The results obtained in the research show that tensiometers and their use at plot level show significant advantages in determining the timing of irrigation because it intervenes with several parameters, it is compact and the data obtained are in situ (real field conditions) which increases its efficiency. The Penman-Monteith equation uses climatological data and other parameters, the values obtained are of evapotranspiration of the reference crop, which allows determining when and how much to irrigate, the tensiometer provides real information, it does not need any calculation or knowledge, just a reading. It is concluded that tensiometers are tools that can be used in any production system.